Posttranscriptional regulation of adrenal TH gene expression contributes to the maladaptive responses triggered by insulin‐induced recurrent hypoglycemia. Issue 2 (23rd February 2015) - Kudrick, Necla; Chan, Owen; La Gamma, Edmund F.; Kim, Juhye Lena; Tank, Arnold William; Sterling, Carol; Nankova, Bistra B.
Abstract Acute metabolic stress such as insulin‐induced hypoglycemia triggers a counterregulatory response during which the release of catecholamines (epinephrine), the activation of tyrosine hydroxylase (TH) enzyme and subsequent compensatory catecholamine biosynthesis occur in the adrenal medulla. However, recurrent exposure to hypoglycemia (RH), a consequence of tight glycemic control in individuals with type 1 and type 2 diabetes compromises this physiological response. The molecular mechanisms underlying the maladaptive response to repeated glucose deprivation are incompletely understood. We hypothesize that impaired epinephrine release following RH reflects altered regulation of adrenal catecholamine biosynthesis. To test this hypothesis, we compared the effect of single daily (RH) and twice‐daily episodes of insulin‐induced hypoglycemia (2RH) on adrenal epinephrine release and production in normal rats. Control animals received saline injections under similar conditions (RS and 2RS, respectively). Following 3 days of treatment, we assessed the counterregulatory hormonal responses during a hypoglycemic clamp. Changes in adrenal TH gene expression were also analyzed. The counterregulatory responses, relative TH transcription and TH mRNA levels and Ser40‐TH phosphorylation (marker for enzyme activation) were induced to a similar extent in RS, 2RS, and RH groups. In contrast, epinephrine and glucagon responses were attenuated in the 2RH group and this was associated with a limited elevation of adrenal TH mRNA, rapid inactivation of TH enzyme and no significant changes in TH protein. Our results suggest that novel posttranscriptional mechanisms controlling TH mRNA and activated TH enzyme turnover contribute to the impaired epinephrine responses and may provide new therapeutic targets to prevent HAAF.